A Post Hoc Analysis of KidneyIntelX and Cardiorenal Outcomes in Diabetic Kidney Disease. Issue 9 (29th September 2022) - Nadkarni, Girish N.; Takale, Dipti; Neal, Bruce; Mahaffey, Kenneth W.; Yavin, Yshai; Hansen, Michael K.; Fleming, Fergus; Heerspink, Hiddo J.L.; Coca, Steven G.
Abstract : Key Points: KidneyIntelX, a bioprognostic test for assessing risk of CKD progression, risk stratified individuals for kidney, heart failure, and death outcomes in the Canagliflozin Cardiovascular Assessment Study. Individuals scored as high risk seemed to derive more of benefit from treatment with canagliflozin versus placebo. These findings may serve to increase adoption of underutilized therapies for cardiorenal risk reduction in patients with diabetic kidney disease.